A study on the temperature dependence of characteristics of phase change memory devices - Lee, Suyoun; Jeong, Doo Seok; Jeong, Jeung-hyun; Zhe, Wu; Park, Young-Wook; Ahn, Hyung-Woo; Kim, Mok; Cheong, Byung-ki (AMER INST PHYSICS, 2009)
We investigated the temperature dependence of characteristics of phase change memory devices composed of Ge(2)Sb(2)Te(5) (GST). We found that the RESET resistance (R(R)), SET resistance (R(S)), and SET time (t(SET)) decreased with increasing ambient temperature (T(amb.)) while RESET current (I(R)) increased with T(amb.) These results were explained in terms of the enhanced thermal activation of electrical conduction in GST and the increased thermal conductivity of the bottom electrode with T(amb.). Besides, threshold voltage (V(th)) was found to decrease linearly with T(amb.), seemingly in support of the relaxation semiconductor model and hopping-dominated transport model both of which predicted the existence of critical conductivity for threshold switching in chalcogenide glasses. (C) 2009 American Institute of Physics. [DOI: 10.1063/1.3211872]
Keywords: FILMS; RESISTANCE; ALLOYS